Retinol, retinal and retinoic: making sense of skincare with vitamin A derivatives - Mathad, Vijayashree; Bhaskaran, Hansini; S., Shivprasad (International Journal of Research in Dermatology, 2025)
Background: Topical retinoids such as retinol, retinal, and retinoic acid are widely used for skin rejuvenation. Understanding their skin absorption and molecular effects through non-invasive methods can optimize their therapeutic use while minimizing adverse effects. Methods: This study involved human participants who applied commercially available retinol, retinal, and retinoic acid formulations over 12 weeks. All assessments were non-invasive, utilizing high-resolution skin imaging, optical coherence tomography (OCT), and confocal microscopy to monitor changes in skin structure, pigmentation, and elasticity. Skin responses, absorption levels, and molecular activity were inferred from imaging biomarkers and skin parameter measurements, with ethical approval and informed consent obtained. Results: Data indicated that retinal achieved approximately 25% higher skin penetration compared to retinol (p<0.01). Imaging analyses showed that retinal significantly enhanced skin renewal markers, correlating with a 35% greater reduction in wrinkle depth and a 22% increase in skin elasticity versus retinol. Participants using retinoic acid experienced rapid improvements within 4 weeks but reported higher rates of skin irritation (p<0.01). Overall, retinal demonstrated a favorable balance of efficacy and tolerability based on non-invasive assessments. Conclusions: Non-invasive imaging and biomarker analysis suggest that retinal is an effective and well-tolerated topical agent for skin rejuvenation, providing superior skin improvements with minimal adverse effects. These findings support the potential of retinal as a preferred retinoid formulation in clinical skincare applications.